Feasibility of Cosmetic Etnobotany-Based Pocketbook in Tonang Village as A Biology Learning Resource in High School - Julkrisno Julkrisno; Syamswisna Syamswisna; Andi Besse Tenriawaru (Journal of Biology Learning, 2022)
This study aims to determine the types of plants used as cosmetic ingredients by the people of Tonang Village, SengahTemila District, Landak Regency. The results of research on cosmetic plants are presented in the form of learning media in the form of a pocket book. The type of this research is qualitative and quantitative with descriptive method using triangulation data collection technique. The number of informants used were 76 informants with characteristics based on gender, age, education and occupation. Data analysis used descriptive analysis using media validation sheets. The results of cosmetic plants obtained were 21 species with 18 families with the most habitus being trees.The most locations found cosmetic plants in the yard of the house, the part that is widely used is leaves, the method of use is mostly by sticking it. Cosmetic plants are believed to have a beautiful effect on themselves such as smoothing and whitening facial skin, removing acne and thickening hair.The validation of pocket book media in Tonang Village was validated with 3 aspects and 12 criteria, so that the contents of pocket book media were declared feasible with an average total CVI validation of 0.99.